Evaluating measures of jobs–housing proximity and their commuting impacts in Shanghai - Yue, Liying; Li, Kaiming; Zhang, Yingqing (Frontiers in Built Environment, 2025)
A long-running controversy arises over the magnitude of the effect of jobs–housing proximity on commuting length. Different views may stem in part from the inconsistency of the selection of jobs–housing proximity measures. Job–worker ratio, minimum commuting, and job accessibility are three common proxies for jobs–housing proximity. This paper analyzed and compared the magnitude of these measures on average commuting distance for all workers and five occupational worker subgroups, based on the national 1% Population Sample Survey in Shanghai. The results indicate that, in contrast to studies in developed countries, job accessibility has the strongest explanatory power for average commuting distance, and job–worker ratio is the weakest one, followed by minimum commuting. Residential location follows patterns of average job location rather than that of the closest available job location in Shanghai. Each measure is valuable in characterizing the spatial proximity between jobs and housing and can provide important information and guidance to policymakers on jobs–housing proximity. This study highlights that improving the jobs–housing balance is an effective way to reduce commuting length, but the magnitude of the impact varies with the category of measures and worker subgroups. In order to make the jobs–housing balance an effective planning tool with which to shorten commuting, land use patterns at the local and regional levels must be spatially linked and coordinated.